Enforcing downward accountability for nonprofit effectiveness: a case study of Malaysian NGO - Mohd Noor, N.H. (2015)
The paper aims to examine the influence of three main downward accountability approach; information disclosure, participation mechanism, and complaints procedures on the external and internal effectiveness of nonprofit organizations in Malaysia. This study also seeks to provide a comprehensive measurement of downward accountability. A random sampling and a structured questionnaire survey were employed in approaching 300 staffs of 30 nonprofit organizations located in Klang Valley area, Malaysia. A total of 209 responses were received (69.6% of the response rate). A descriptive analysis and a structural equation modeling by SPSS AMOS were used for data analysis and hypotheses testing. The results revealed that information disclosure and complaints procedures affect both external and internal effectiveness except for participation mechanism. The results provide a theoretical and methodological contribution to the study of nonprofit accountability and add value to the current research.